ANALISIS PERBANDINGAN TARIF PAJAK PENGHASILAN PASAL 17 DAN TARIF PAJAKPENGHASILAN PASAL 4 AYAT 2 (STUDY KASUS PADA CV. MELANIA) - Ransulangi, Marcelino; Karamoy, Herman; Pangerapan, Sonny (Universitas Sam Ratulangi, 2016)
Income tax (VAT) is a tax levied on income earned by a taxpayer or entity. Income tax article 17 and article 4, paragraph 2 is one of the taxes that are used by the taxpayer or the body to calculate the tax to be paid to the government. The purpose of this study was to determine and analyze the process of calculation of Income Tax Article 17 and Article 4 paragraph 2 so that taxpayers can know the magnitude comparison of tax payments by using Tax Article 17 and Income Tax Article 4, paragraph 2 also taxpayers can determine the article where the right to apply in the company. The research was conducted in the city of Manado on the CV. Melania. The method used in this research is descriptive method. Data collection techniques that will be done is by way of literature research, documentation, and interviews. Keywords: Income Tax, Income Tax Article 17, Income Tax Article 4 paragraph 2.